B2B STRATEGY IN INCREASING REVENUE AND PRODUCT PROMOTION OF TEMPE HOME INDUSTRY EROWATI SEMARANG - Dita Aulia; Nina Mistriani; Bintang Destian Nugraha; Satri Wati Bunawolo; Umar Faruq (Sahid University Jakarta, 2024)
Business to business is a sales process carried out by one business to another business with a cooperationagreement to obtain the same income. In this case, the tempe home industry has implemented a B2Bstrategy with a system of marketing the results of the tempe business directly to tempe entrepreneurs andtraditional markets in Semarang. This research aims to describe the strategy of the tempe householdindustry in increasing its potential, development and obstacles faced as well as solutions. This researchmethod uses a descriptive qualitative approach. The research results show that: (1) The level ofproduction failure in the tempe making process can occur when target market identification, relevantproduct offerings, pricing and purchasing conditions are not established, and strategic partnerships arenot established. Thus, resulting in low income, (2) Marketing is essential for MSME businesses includingthe use of social media and websites, use of social media and websites, special offers and trials throughcreative tourism models, namely educational tourism.